MARKETING COMMUNICATION STRATEGY IMPLEMENTATION OF NOVEL “REIVAN AND REINA” BY CHRISTA BELLA IN INTERNET COMMUNITY FORUM - Supriyanto Supriyanto (Metakom, 2019)
This study aims to determine the process of marketing communication strategy novel